2020
DOI: 10.1016/j.seizure.2020.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Neurocysticercosis in people with epilepsy in Sub-Saharan Africa: A systematic review and meta-analysis of the prevalence and strength of association

Abstract: We analyzed studies on neurocysticercosis (NCC) and epilepsy across Sub-Saharan Africa (SSA) to determine the prevalence of NCC in people with epilepsy (PWE) and the strength of association of NCC with epilepsy in the region. Methods: We conducted a systematic review of the existing literature on NCC and epilepsy in SSA. Diagnostic methods for NCC in the studies selected for our analysis included one or more of the following: positive brain CT, serum ELISA and serum EITB. A common prevalence and overall odds-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…Over three-fourths of persons having epilepsy live in the LMICs, and about two-thirds of these cases have unknown etiology (167,170). Although some reports suggest a relationship between epilepsy and CNS infections in Africa (168,172), the etiology of most epilepsy remains unknown. This emphasizes the role of genetics and an urgent need for genetic investigations.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…Over three-fourths of persons having epilepsy live in the LMICs, and about two-thirds of these cases have unknown etiology (167,170). Although some reports suggest a relationship between epilepsy and CNS infections in Africa (168,172), the etiology of most epilepsy remains unknown. This emphasizes the role of genetics and an urgent need for genetic investigations.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…Nevertheless, clinical assessment of PWE in our study population of Balaka district, yielded a rather low prevalence of NCC (less than 6%). Other studies in endemic areas including sub-Saharan Africa reported significantly higher prevalence estimates of symptomatic NCC in PWE ranging up to 20–40%, varying with geographic regions and the method of diagnosis [ 4 , 13 , 34 ]. Reasons for this low prevalence may be that the Muslim population in the district was higher than anticipated and pork consumption was lower than anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…However, in sub-Saharan Africa, access to modern anti-seizure medicine is limited for many people and a lack of awareness and education concerning epileptic seizures and epilepsy combined with traditional beliefs and subsequent social stigma lead to underdiagnosis and a large treatment gap of the disease [ 13 , 14 ]. Hence, before implementing MDA, it is important to estimate what proportion of PWE are associated with NCC, which could indicate the extent to which a relatively large number of people are likely to have asymptomatic undiagnosed active NCC.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Over 80% of the global burden of epilepsy is in low-and middle-income countries (LMICs), where secondary causes of epilepsy such as neurocysticercosis and traumatic brain injuries are highly prevalent. 1,3 Epilepsy has for long been misunderstood as a disease of the young, however, both the incidence and prevalence of epilepsy increase throughout adulthood. 4,5 In fact, the incidence of seizures and epilepsy in the elderly population is increasingly being recognized and constitutes a significant proportion of the global burden of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…1 , 2 Over 80% of the global burden of epilepsy is in low- and middle-income countries (LMICs), where secondary causes of epilepsy such as neurocysticercosis and traumatic brain injuries are highly prevalent. 1 , 3 …”
Section: Introductionmentioning
confidence: 99%